A COMPARATIVE STUDY OF VAGINAL PROSTAGLANDIN E2 PESSARIES WITH INTRAVENOUS OXYTOCIN FOR THE INDUCTION OF LABOUR AFTER SPONTANEOUS RUPTURE OF MEMBRANES - Riaz, G. Sarwar; Saeed, Fauzia (Journal of Ayub Medical College Abbottabad, 1991)
ABSTRACT: In a prospective randomized study, 60 patients were induced with 3 mg vaginal FE2 pesseries or intravenous oxytocin. Oxytocin stimulation was associated with shorter labour and a lower incidence of abnormal cervimeteric progress, after spontaneous rupture of membranes. Out of these patients given PGE2 20% required a second dose after four hours of slow progress. 10% of primigravida subsequently developed abnormal labour and required augmentation by oxytocin to correct their uterine contractions. Two caesarian sections were carried out for disproportion and remaining 58 patients were delivered vaginally. PGE2 pesseries were not associated with an increased incidence of hyperstimulation or sepsis. In conclusion oxytocin infusion is a safe, effective but inconvenient method of induction of labour, while PGE2 pesseries are safe, effective, more acceptable but an expensive method of induction of labour.